2008
DOI: 10.3136/fstr.14.565
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Mustard and Hop Extract Agents with Emulsifier on Microbial Quality and Physiology of Fresh-cut Vegetables

Abstract: Cabbage shreds and cucumber slices were dipped in water or solution of mustard extract agent (MEA) and hop extract agent (HEA) with or without sucrose fatty acid ester (SE) and stored in an MA package at 10℃. With cabbage shreds, counts of mesophiles and coliforms were 0.3 to 0.7 logs lower in samples treated with MEA with or without SE than with the water-dipped control for the first 2 days of storage. However, MEA accelerated the growth of lactic acid bacteria. When HEA was combined with MEA and SE, growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Previous indications have shown that lettuce produces very little ethylene and at the same time it is sensitive to the presence of ethylene [ 3 ]. Interestingly, Hamanaka and Izumi [ 57 ] examining the effects of mustard and hop extracts on shredded cabbage and sliced cucumber reported lower respiration rates and ethylene production in both products.…”
Section: Discussionmentioning
confidence: 99%
“…Previous indications have shown that lettuce produces very little ethylene and at the same time it is sensitive to the presence of ethylene [ 3 ]. Interestingly, Hamanaka and Izumi [ 57 ] examining the effects of mustard and hop extracts on shredded cabbage and sliced cucumber reported lower respiration rates and ethylene production in both products.…”
Section: Discussionmentioning
confidence: 99%